Rama interpretacyjna dotyku w języku polskim = The interpretative framework of the sense of touch in the Polish language - Kładoczny, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
People reproduce the experiences of their cognition in words that one combines into meaning complexes. A collection of semantic categories that describe a specific range of human activity is called a semantic framework. With this method, it is possible to describe the experience of human perception.
Keywords: percepcja; zmysły; dotyk; konceptualizacja; rama semantyczna; perception; senses; touch; conceptualisation; semantic frame